Stand up! : how to get involved, speak out, and win in a world on fire - Whitman, Gordon (Berrett-Koehler Publishers, 2018)
For those frustrated by what they see happening in the world but not sure what they can do about it, this book describes five types of conversations that enable people to build organizations that can solve local problems and confront the greatest challenges facing our country. --